GIZI PENENTU TUMBUH KEMBANG ANAK - Reistanti, Tista (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Nutritional adequacy and food is one important factor in improving the quality of human resources , which is a key factor in the successful development of a nation . Healthy and normal child will grow and develop according to its genetic potential . Growth have an impact on the physical aspect , while the developments related to the maturation of organ function or individual . A childs growth is also influenced by nutrient intake obtained from the food consumed . Food consumption is one of the basic needs that your body needs every day in a certain amount as a source of energy and nutrients . Deficiency or excess in the long term will be bad for health . Energy needs and nutritional substances depends on various factors , such as age , gender , body weight , climate , and physical activity . Deficiency or excess nutrients consumed by a child will have an impact in the growth and development that deviates from the standard pattern should be. The final impact of the consumption good and balanced nutrition is to improve the quality of human resources . Keywords : Nutrition , Growth